Comparative study of the bearing capacity of square and rectangular shallow foundations based on Terzaghi and Meyerhof methods - Sayed Ahmad Fauzan; Ricky Harianja; Ekodjati Tunggulgeni; Okri Asfino Putra; Muhammad Hamzah Fansuri; Pungky Dharma Saputra; Suprayogi Suprayogi; Fadhil Muhammad Nuryanto (Fakultas Teknik dan Teknologi Pertahanan, Universitas Pertahanan Republik Indonesia, 2026)
Foundation integrity is paramount in evaluating building reliability. This research investigates Building X, a two-story structure with shallow footing foundations on soft soil in East Jakarta. The study compares bearing capacity using Terzaghi and Meyerhof methods, with structural loads modeled in ETABS. Results show Terzaghi’s ultimate bearing capacity (qu) is 15076.00 kg/m2, while Meyerhof’s is 22017.68 kg/m2. Consequently, Terzaghi provides a more conservative Safety Factor (SF). The technical implications are critical for decisions: Terzaghi’s results serve as a lower-bound safety limit to prevent catastrophic shear failure, while Meyerhof offers comprehensive geometry-based parameters. Many points exhibit an SF below the 3.00 standard, with several below 1.00 under Terzaghi analysis. This study contributes to building audits by bridging classical theories with practical Building Functionality Certificate (SLF) requirements in soft soil regions. The findings underscore the necessity for future numerical validation using Plaxis 2D to account for complex non-linear soil-structure interactions and precise settlement behavior.